Dynamics of LV myocardial perfusion according to volumetric CT of the heart with a pharmacological test with ATP in comparison with clinical manifestations of stable coronary heart disease, risk factors and the nature of drug therapy in patients with non-obstructive coronary heart disease - O. F. Egorkina; G. N. Soboleva; S. A. Gaman; S. K. Ternovoy (Евразийский Кардиологический Журнал)
Aim: to evaluate the parameters of left ventricle (LV) myocardial perfusion using volumetric computed tomography (VCT) of the heart with an adenosine triphosphate (ATP) test in patients with coronary artery disease with non-obstructive lesions of the coronary arteries (INOCA) over time against the background of optimal drug therapy (ODT). Material and methods. The study of VCT of the heart with ATP, combined with   CT-CAG, was carried out at 2 points in 46 patients with an established diagnosis of INOCA. The study protocol included myocardial perfusion at rest and against the   background of a pharmacological load of ATP at the rate of 160 mcg/kg/min with   an infusion duration of 3-5 minutes. Results. There was no significant difference in the median number of LV myocardial segments with perfusion defects (DP) assessed over time (4.5 [3;7] vs 4[3;8],   p=0.751). However, in patients adherent to therapy, compared with patients who did not comply with the ODT regimen, there was a statistically significant difference in the change in the number of segments with DP over time (−1 vs +2 segments, p=0.020). In dynamics, the global coefficient of transmural perfusion (TPR) did not increase statistically significantly: at rest – mean difference 0,00 [95%CI −0,02;   0,01], p=0.7, with stress – mean difference 0.01 [95%CI 0,00; 0.02], p=0.2. At the same time, it is noteworthy that patients with worsening TPR were less adherent to the prescribed ODT. Against the background of ODT, there was a significant positive dynamics in improving the quality of life according to the average value of all scales of the questionnaire (69±17 vs 75±14, p=0,006). MACE during long-term follow-up occurred in 2 %. Conclusion. In patients with INOCA, against the background of ODT, positive dynamics are observed in the form of improved parameters of LV myocardial perfusion, according to cardiac VCT with ATP, and improved quality of life over time.